2014
DOI: 10.1371/journal.pone.0087040
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Metabonomic for a Gateway Drug: Nicotine Priming Enhances Behavioral Response to Cocaine with Modification in Energy Metabolism and Neurotransmitter Level

Abstract: Nicotine, one of the most commonly used drugs, has become a major concern because tobacco serves as a gateway drug and is linked to illicit drug abuse, such as cocaine and marijuana. However, previous studies mainly focused on certain genes or neurotransmitters which have already been known to participate in drug addiction, lacking endogenous metabolic profiling in a global view. To further explore the mechanism by which nicotine modifies the response to cocaine, we developed two conditioned place preference (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 57 publications
2
27
0
1
Order By: Relevance
“…The rats were made dependent by chronic, intermittent exposure to alcohol vapors as previously described (O'Dell et al, 2004;Gilpin et al, 2008). They underwent cycles of 14 h on (blood alcohol levels during vapor exposure ranged between 150 and 250 mg%) and 10 h off, during which behavioral testing for acute withdrawal occurred (i.e., 6 -8 h after vapor was turned off when brain and blood alcohol levels are negligible; Gilpin et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rats were made dependent by chronic, intermittent exposure to alcohol vapors as previously described (O'Dell et al, 2004;Gilpin et al, 2008). They underwent cycles of 14 h on (blood alcohol levels during vapor exposure ranged between 150 and 250 mg%) and 10 h off, during which behavioral testing for acute withdrawal occurred (i.e., 6 -8 h after vapor was turned off when brain and blood alcohol levels are negligible; Gilpin et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…They underwent cycles of 14 h on (blood alcohol levels during vapor exposure ranged between 150 and 250 mg%) and 10 h off, during which behavioral testing for acute withdrawal occurred (i.e., 6 -8 h after vapor was turned off when brain and blood alcohol levels are negligible; Gilpin et al, 2009). In this model, rats exhibit somatic withdrawal signs and negative emotional symptoms, reflected by anxiety-like responses and elevated brain reward thresholds (Schulteis et al, 1995;Roberts et al, 2000;Valdez et al, 2002;O'Dell et al, 2004;Sommer et al, 2007;Edwards et al, 2012). Nondependent rats were not exposed to alcohol vapor.…”
Section: Methodsmentioning
confidence: 99%
“…This period of life is a very sensitive age in which the negative affective state associated with nicotine withdrawal is reduced while the rewarding action of nicotine is enhanced compared to adults (Carcoba et al, 2014;Dickson et al, 2014;Dickson et al, 2011;Hutchison and Riley, 2008;Lee et al, 2015;McQuown et al, 2009;Natividad et al, 2012;Natividad et al, 2010;Natividad et al, 2013;O'Dell et al, 2004;O'Dell et al, 2006;O'Dell et al, 2007;Shram et al, 2008;Torres et al, 2008;Wilmouth and Spear, 2004), making adolescents a vulnerable target to nicotine use and abuse as well as for use of other addictive drugs during adulthood. Consistent with this notion, previous studies have shown that nicotine exposure during adolescence can prime the use and abuse of cocaine, alcohol, and other addictive substances (Bechtholt and Mark, 2002;DiFranza and Guerrera, 1990;Horger et al, 1992;Hutchison and Riley, 2008;Kandel and Kandel, 2015;Kandel and Kandel, 2014;Kelley and Rowan, 2004;Kouri et al, 2001;Levine et al, 2011;Li et al, 2014;McQuown et al, 2007;McQuown et al, 2009;Meliska et al, 1995;Natividad et al, 2010;Rinker et al, 2011;Rosenberg, 2014;Schindler et al, 2012;Schneider et al, 2012). There is also evidence showing that about 90% of regular smokers start using tobacco at an early age, and that early onset smoking carries a major risk for the development of addiction to other drugs of abuse (Rimm et al, 1995).…”
Section: Introductionmentioning
confidence: 78%
“…Many studies have reported that nicotine may serve as a gateway drug for cocaine and other illicit drugs (Dickson et al, 2014;Dickson et al, 2011;Levine et al, 2011;Li et al, 2014;McQuown et al, 2007;Orsini et al, 2008). However, there is limited information on the effect of nicotine treatment on the rewarding action of cocaine if nicotine is administered during adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation